Limited impacts of climatic conditions on commercial oil palm yields in Malaysian plantations - Susannah Fleiss; Colin J. McClean; Henry King; Jane K. Hill (CABI Agriculture and Bioscience)
Abstract Background Oil palm is a key driver of deforestation, but increasing yields in existing plantations could help meet rising global demands, while avoiding further conversion of natural habitat. Current oil palm plantations present substantial opportunities for sustainable intensification, but the potential for local yield improvements depends partly on the role of climate in determining yield. Methods We determine the importance of local climatic conditions for oil palm yields in 12 commercial plantations in Peninsular and East Malaysia (Borneo), during 2006–2017. We quantify relationships between climatic conditions (raw and anomalised monthly temperature and rainfall data) and yield for lag times up to 36 months prior to harvest, corresponding to key stages in oil palm fruit development. Results Overall, climatic conditions explained < 1% of the total variation in yield. In contrast, variation in yield among plantations accounted for > 50% of the explained variation in yield (of total R 2 = 0.38; median annual fresh fruit bunch yield 16.4–31.6 t/ha). The main climatic driver of yield was a positive effect of maximum monthly temperature during inflorescence development (Spearman’s Rho = 0.30), suggesting that insufficient solar radiation is the main climatic constraint to yield in our study sites. We also found positive impacts of rainfall during key stages of fruit development (infloresence abortion and sex determination: Spearman’s Rho 0.06 and 0.08 respectively, for rainfall anomalies), suggesting minor effects of water-limitation on yield; and a negative impact of maximum temperature during the month of harvest (Spearman’s Rho – 0.14 for temperature anomalies), suggesting possible heat stress impacts on plantation workers. Conclusions Our findings imply a relatively minor role of climate in determining yield, and potentially substantial yield gaps in some commercial plantations in Malaysia (possibly up to ~ 50%). Thus, there appear to be substantial opportunities for improving oil palm yield in existing plantations in Malaysia, with further research needed to identify the drivers of such yield gaps.